Answer:
x = 1
y = 3
Explanation:
Substitution Method:
Step 1:
Name The Equation
4x + y = 7 ...(1)
3x + 2y = 9 ...(2)
Step 2:
From Equation (1) we get,
4x = 7 - y
i.e.,
x = 7 - y/4
Step 3:
Substitute the value of x = 7 - y/4 in equation (2)
i.e.,
3(7 - y/4) + 2y = 9
21 - 3y/4 + 2y = 9
21 - 3y + 8y/4 = 9
21 - 3y + 8y = 9 * 4
21 + 5y = 36
5y = 36 - 21
5y = 15
y = 15/5
y = 3
Step 4:
Substitute the value of y = 3 in equation (1)
4x + y = 7
i.e.,
4x + (3) = 7
4x + 3 = 7
4x = 7 - 4
4x = 4
x = 4/4
x = 1
Verification:
4x + y = 7 i.e., 4(1) + (3) = 7
3x + 2y = 9 i.e., 3(1) + 2(3) = 9